2016
DOI: 10.3390/met6070170
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Grain Refinement of Al-Si Alloy Solidified under the Impact of Pulsed Electric Current and Travelling Magnetic Field

Abstract: Abstract:It is high of commercial importance to generate the grain refinement in alloys during solidification by means of electromagnetic fields. Two typical patterns of electromagnetic fields, pulsed electric currents (ECP) and traveling magnetic field (TMF), are frequently employed to produce the finer equiaxed grains in solidifying alloys. Various mechanisms were proposed to understand the grain refinement in alloys caused by ECP and TMF. In this paper, a comparative study is carried out in the same solidif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 27 publications
0
14
0
4
Order By: Relevance
“…Practically, when the solid fraction exceeds a threshold value, the dendrites start to become a coherent network and the free grains are so large that only smaller ones can pass through the network, thus, leaving the large grains pinned in the solid skeleton and the feeding path blocked prematurely. When TMF is introduced, the solid skeleton is likely to be broken up by the imposed Lorentz force during solidification, and the grains are refined [18]. Moreover, due to the stirring effects of the TMF, the distribution of solutes becomes more uniform, which are helpful to precipitate equiaxed grains instead of the solid skeleton [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Practically, when the solid fraction exceeds a threshold value, the dendrites start to become a coherent network and the free grains are so large that only smaller ones can pass through the network, thus, leaving the large grains pinned in the solid skeleton and the feeding path blocked prematurely. When TMF is introduced, the solid skeleton is likely to be broken up by the imposed Lorentz force during solidification, and the grains are refined [18]. Moreover, due to the stirring effects of the TMF, the distribution of solutes becomes more uniform, which are helpful to precipitate equiaxed grains instead of the solid skeleton [19].…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the TMF can change the micro-pore morphology, and this change is mainly caused by the shape of the primary solid skeleton. Although many research reports [14,18,20] have studied the grain refining under the magnetic field, the relationship between the grain refining and porosity has not been revealed. In this work, we found that refining the grain size can improve the feeding ability in the solidification progress and decrease the volume fraction of the porosity under TMF, suggesting a promising process to improve the quality of the casting Al-alloy.…”
Section: Resultsmentioning
confidence: 99%
“…It is located just below BL. In terms of microstructure, WL is formed by nanocrystalline martensite as a result of high discharge energy and subsequent rapid quenching by dielectric fluid [23,24]. The resulting martensitic structure is involved in extreme growth of microhardness in WL, up to the level of 600 HV 2.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of cast alloys can be enhanced by grain refinement or microstructure modification. In the past decades, various physical fields such as electric current pulse (ECP) [1][2][3][4][5][6], ultrasonic vibration [7][8][9][10] and electromagnetic stirring [11][12][13][14][15] have been applied during the solidification of alloys in order to refine the solidification structure. Recently, there has been much progress in ECP treatment, and much attention has been attracted to revealing the mechanism of ECP on grain refinement of alloys.…”
Section: Introductionmentioning
confidence: 99%